2014
DOI: 10.1002/2013jd020900
|View full text |Cite
|
Sign up to set email alerts
|

Change in the contribution of spring snow cover and remote oceans to summer air temperature anomaly over Northeast China around 1990

Abstract: Sea surface temperature (SST), snow cover, and soil moisture anomalies are factors for climate variability over land regions. The present study found that the relationship between in situ spring snow cover and Northeast China summer surface temperature variations is not steady. It is significant during mid-1970s through late 1980s but weak during the 1990s and 2000s. This interdecadal change in the spring snow cover-summer temperature relationship is found to relate to the effects of SST anomalies in the tropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 52 publications
1
26
0
Order By: Relevance
“…The persistence of the wave train in the wind difference fields over Eurasia is a suggestion of possible lower boundary forcing on atmospheric circulation. The circulation anomalies over Eurasia have been linked to the North Atlantic SST anomalies in previous studies [ Z. Wu et al ., ; Wu et al ., , , ]. Recently, tropical North Atlantic SST anomalies are shown to excite a Rossby wave pattern propagating from western tropical Atlantic to Europe, thereby influencing the southeastern Europe winter precipitation [ Hatzaki and Wu , ].…”
Section: Atmospheric Circulation Change and Roles Of Equatorial Atlanmentioning
confidence: 99%
“…The persistence of the wave train in the wind difference fields over Eurasia is a suggestion of possible lower boundary forcing on atmospheric circulation. The circulation anomalies over Eurasia have been linked to the North Atlantic SST anomalies in previous studies [ Z. Wu et al ., ; Wu et al ., , , ]. Recently, tropical North Atlantic SST anomalies are shown to excite a Rossby wave pattern propagating from western tropical Atlantic to Europe, thereby influencing the southeastern Europe winter precipitation [ Hatzaki and Wu , ].…”
Section: Atmospheric Circulation Change and Roles Of Equatorial Atlanmentioning
confidence: 99%
“…A decrease in LH over northern Europe, the eastern European Plain, and western Siberia (Fig. 3, but for anomalies regressed on the normalized PC2 of MAM SAT during 1979-2010 SWE is compensated by the cloud-albedo effect associated with an increase in TCC (Figs. 2a,c).…”
Section: B Surface Heat Flux Anomaliesmentioning
confidence: 99%
“…Wu et al 2009;R. Using observational data and model simulations, previous studies have indicated that a tripole North Atlantic SST anomaly pattern can excite a wave train extending eastward from the North Atlantic to East Asia along the westerly jet waveguide (e.g., Z.…”
Section: B Roles Of Ao and North Atlantic Sst Anomaliesmentioning
confidence: 99%
See 2 more Smart Citations